Synaptic and extrasynaptic NMDA receptors in hippocampal neurons: regulation of nuclear shape and cell fate - Wittmann, Malte (2006)
Neuronal activity induces processes important for memory formation and cell survival by inducing calcium influx through synaptic NMDA receptors. Calcium subsequently activates the ERK-MAP kinase cascades that transmits the signal from the synapse to the nucleus. A second mode for synapse-to-nucleus communication involves a propagating calcium signal that invades the cell nucleus. Nuclear calcium is a key regulator of gene expression mediated by the transcription factor CREB. The nuclear architecture contains intranuclear structures that have been shown to facilitate calcium influx into the nucleus. This thesis describes a novel mechanism in which calcium influx through NMDA receptors induces morphological changes in the majority of hippocampal neurons by forming infoldings of the nuclear membrane. These infoldings are generated by an increase in the surface area of the nuclear membrane and require activation of the ERK-MAP kinase cascade as well as a nuclear calcium signal. Infoldings are formed rapidly within one hour and can be reversed by silencing of synaptic activity. The stability of infoldings increases within days after activation of synaptic NMDA receptors, suggesting the involvement of gene transcription in the stabilization process. Synaptic activity is counteracted by overactivation of extrasynaptic NMDA receptors. Calcium influx through these receptors leads to a rapid loss of nuclear infoldings. It also activates pathways leading to the shut-off of CREB and to cell death. I attempted to dissect the intracellular pathways downstream of synaptic and extrasynaptic NMDA receptors by designing a specific antagonist for extrasynaptic NMDA receptors. This should be achieved by coupling of Conantokin-G, a peptide antagonist against the NR2B subunit of NMDA receptors, to beads of a specific size. The peptide coupled to beads should allow blockade of extrasynaptic NMDA receptors and thereby block cell death pathways, leaving synaptic NMDA receptors unaffected.
Keywords: Hochschulschrift